BORE PILE FOUNDATION BEHAVIOR ANALYSIS IN MUD FLOW AREA (Case Study In Margamukti Village, Pangalengan-Bandung Regency) - Nugraha, Akbar; Suhirman, Agi; Adevia, Shinta; Evanka, Qory Sarah; Setiawan, Asep (CENTRAL ASIA AND THE CAUCASUS, 2022)
Cracks in the soil in Margamukti village, Pangalengan, Bandung Regency caused a landslide and hit 3 pipes belonging to PT. Star Energy Geothermal so that the pipe breaks and releases hot steam. The installation of the bore pile foundation is a solution to support the 3 geothermal pipes and to withstand the movement of mud flows (colluvial soil). In this study, the researchers used two methods, namely the poulos method at a depth of 0-8 m and then continued by using the Reese & Matlock method at a depth of 8 - 35 m to determine whether the bore pile is strong enough to withstand the flow of mud. The results of the use of these two methods are then compared with the maximum allowable moment of the quality of the concrete used as a bore pile material, which is fc' = 25 MPa. Based on the results of the analysis, it is found that the maximum moment of the bore pile obtained from the Poulos and Reese & Matlock method does not exceed the maximum allowable moment, so that the bore pile is safe.